Mesoporous silica nanoparticles as targeted drug delivery carriers - Karol Przemysław Nartowski; Karolina Krajewska (Polish Pharmaceutical Society, 2022)
Targeted anticancer therapies using nanomaterial-based systems enable the delivery of therapeutic substances directly to the cancer cell. Unfortunately, cellular uptake of anticancer drugs is often low and the used active substances are poorly soluble or chemically or physically unstable. Another challenge comes with the limited selectivity of anticancer drugs which translates into their systemic toxicity and the occurrence of many dangerous side effects, significantly hindering the patient's quality of life. The potential solution is to encapsulate the drug in a carrier that could selectively bind to the receptor on the cancer cell. Recently, major advancements can be observed in drug delivery technology using various nanocarriers. This has resulted in an increased demand for materials with stable chemical, physical and mechanical properties. Mesoporous Silica Nanoparticles (MSN) are promising materials with potential application for targeted drug delivery. MSN are porous materials with a size of about 100 nm, high specific surface area and permeability to liquids and gases. Their properties - morphology, particle size, porosity - can be controlled by changing the reactants, their molar ratios or synthesis conditions. All of this makes them ideal candidates as drug carriers. Drug loading may be carried out using an array of methods with physical adsorption from solution being the most commonly used. Controlled surface area and pore size allow to achieve high drug concentration inside the MSN. By attaching specific ligands to the surface of the nanoparticles the carriers can be targeted to a selected receptor located on the membrane of the cancer cell while limiting the effect on neighbouring healthy cells. There is increasing number of reports on the MSN development for biomedical applications. Despite the large number of studies on the biodistribution and biocompatibility of these materials, their behaviour in the body is still not fully understood which significantly limits their development towards clinical applications. This review summarizes and discusses the current state of knowledge about mesoporous silica nanoparticles. The first part of the manuscript discusses the synthesis and functionalization of silica nanoparticles and the influence of various factors on these processes. The second part of the manuscript is summarizes selected examples of MSN as drug delivery systems and discuss their behaviour in the body.